Adsorption Study of Crystal Violet Using Natural Zeolite of Indonesia - Hasanah, Aulia (Molekul, 2026)
ABSTRACT. Indonesia has a lot of Natural Zeolite potential, one of which is Ende’s natural zeolite(EZ) from Nusa Tenggara Timur Province, which is known to have the main components of mordenite, clinoptilolite, and quartz. EZ can be used as an adsorbent for Crystal Violet(CV) dye waste, which is often used as a dye in the textile industry, veterinary medicine, and dermatology, that can be teratogenic, carcinogenic, and mutagenic. EZ were then tested under three conditions: 100 mesh size(EZ), nano-modification with planetary milling using alumina balls (200 rpm/12 hours)(EZN), and recrystallization(EZM). Each EZ were characterized by XRF, FTIR, SEM, XRD, and Zeta Potential measurements. Optimum conditions for CV adsorption using 0.01 gram of each EZ were achieved at pH 6 and a contact time of 90 min using a volume of 10 mL solution, with the batch method. The CV adsorption process followed the pseudo-second-order adsorption kinetics model and the Langmuir isotherm model with a maximum adsorption capacity of 151.327 mg/g and an R2 value = 0.9635 for EZ, 74.166 mg/g and an R2 value = 0.9128 for sample EZN and a capacity the maximum adsorption was 311.357 mg/g and the R2 value = 0.9752 for sample EZM. The thermodynamic study indicated that the process was spontaneous and endothermic and that the degree of orderliness of the system increased. Keywords: Adsorption, Crystal Violet, Mechanochemistry, Natural Zeolite.